2014
DOI: 10.1097/dss.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing Patterns After Mohs Micrographic Surgery and Standard Excision

Abstract: The retrospective review suggests that opioid prescribing is predicted by characteristics of the surgery (i.e., size, defect repair type, and anatomic location) and characteristics of the surgeon (i.e., age, sex, and practice location) with significant heterogeneity in prescribing habits. The national survey results raise the possibility that patients might not take all prescribed opioid pills after dermatologic surgery. Further investigation is warranted to determine how patients are actually using prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 6 publications
2
28
0
Order By: Relevance
“…Several reports from the primary care literature have found that younger physicians are less confident in their understanding of opioids, less confident with managing pain, and more reluctant to prescribe opioids, seemingly in conflict with the results of this study [ 40 , 41 ]. However, one dermatology study found that younger dermatologists are more likely to prescribe opioids to their patients after Mohs surgery, which is consistent with the findings from this study [ 42 ]. The high outright rates of opioid prescription found in this study, and the discrepancy between younger and older physicians, both highlight opportunities for improved physician education on postoperative pain management and further demonstrates the need for safe analgesic guidelines.…”
Section: Discussionsupporting
confidence: 90%
“…Several reports from the primary care literature have found that younger physicians are less confident in their understanding of opioids, less confident with managing pain, and more reluctant to prescribe opioids, seemingly in conflict with the results of this study [ 40 , 41 ]. However, one dermatology study found that younger dermatologists are more likely to prescribe opioids to their patients after Mohs surgery, which is consistent with the findings from this study [ 42 ]. The high outright rates of opioid prescription found in this study, and the discrepancy between younger and older physicians, both highlight opportunities for improved physician education on postoperative pain management and further demonstrates the need for safe analgesic guidelines.…”
Section: Discussionsupporting
confidence: 90%
“…13 Prior studies on opioid prescribing practices in dermatology suggest limited use of opioids after MMS but are derived from observational studies with limited cohorts of dermatologists and patients. 14,15 In this study, we sought to broaden this evaluation by examining the use and potential complications associated with opioid prescriptions within the US Medicare population.…”
mentioning
confidence: 99%
“…23 While countless factors influenced the opioid epidemic, experts suggest that drug companies' unethical claims 22 and incorrect medical research 24,25 caused this spike in prescription opioid sales and usage. More specific to dermatology, 1 retrospective singlecenter study 8 reported that in 2010, 35% of an institution's dermatologic surgery patients received an opioid prescription after their surgical encounter. This parallels our study, which reports that 34.6% to 39.6% of patients who underwent MMS obtained an opioid from 2009 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite evidence that nonopioid analgesics control pain after Mohs micrographic surgery (MMS) 4,5 and consensus recommendations to reserve opioids as a second-line treatment for postsurgery pain, 6,7 15.5% to 58% of patients still receive an opioid prescription after MMS or conventional excisions. 4,8,9 Adequate patient pain management must be delicately balanced with the potential negative consequences of pre-scription opioids. From 1999 to 2011, opioid pharmaceutical sales in the US increased 400%, and prescription opioidrelated deaths surpassed deaths due to heroin and cocaine combined.…”
mentioning
confidence: 99%